PELAKSANAAN BESTUURSDWANG DALAM BIDANG PERIZINAN (Suatu Studi Dalam Konteks Hukum Lingkungan) - W.M. Herry Susilowati (Perspektif, 2002)
License is an instrument that the most widely used in public administration law. The implementation of administrations sanction (bestuursdwang) therefore enable the government to take the administrative action effectively and preventively, It is one of government discretion authority. The instrument has stabilizer, perfective and corrective function to make everyone who conflict or break the law to end their action. Bestuursdwang is the most important law enforcement as it is very effective ‘real action’ (feitelijkhandellingen) that government could make to end the conditions that is prohibited in administrative law. The dissatisfied or suffered party is able to submit beschikking to be examined in PTUN In this content, the judge will act as the invention of law, the former of law, the innovator of law and the executor of law and the fortification of justice. That also happens in living space conservation.